Comparison of nutrient composition and potential feed value of different cakes obtained by cold pressed method - Niyonshuti, E; Kirkpinar, F (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to determine nutrient composition and chemical properties of some cakes obtained by cold pressed method proposed as alternative protein sources, and to reveal their usability in animal feeding. The feed materials used in this study are safflower, black cumin (e and m), flaxseed (e and m), carrot seed, walnut, hempseed, and camelina seed cakes. The proximate analysis, metabolic energies, total phenolic content, total flavonoid and antioxidant activity of these cakes were determined and compared. The average percentage nutrients content of the cakes varies from 95.8 (walnut cake) to 91.9 (flaxseed cake e) for dry matter, from 13.1 (carrot seed) to 3.9 (safflower cake) for crude ash, from 23.5 (flaxseed e cake) to 5.5 (hempseed cake) for ether extract, from 46.8 (flaxseed cake m) to 20.0 (safflower cake) for crude protein, from 45.4 (walnut meal) to 21.9 (safflower cake) for nitrogen-free extract, and from 9.4 (flaxseed m) to 2.2 (safflower cake) for sugar. Starch content was below detectable level in all feed samples. The highest crude fiber was at 37.1, NDF at 52.7, and ADF at 40.4 were found in safflower cake. The highest metabolic energies for poultry (12.8 Mcal kg-1) and for ruminants (14.01 Mcal kg-1) were obtained from black cumin seed cake (e). The highest total flavonoid content (3.15 mg GAE/g) and total flavonoid (2.64 mg QE/g) were found in walnut cake. The antioxidant activity (%) varied from 31.3 for black cumin seed cake (m) to 6.7 for camelina seed cake. Considering the high amount of crude protein (>20%) in the investigated cakes, it is concluded that they can be recommended as alternative protein sources for feeding livestock.